2018
DOI: 10.1155/2018/1729071
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Radiomics: Impact of Pulse Sequence Parameter Selection on MRI-Based Textural Features of the Brain

Abstract: Objectives Radiomic features extracted from diverse MRI modalities have been investigated regarding their predictive and/or prognostic value in a variety of cancers. With the aid of a 3D realistic digital MRI phantom of the brain, the aim of this study was to examine the impact of pulse sequence parameter selection on MRI-based textural parameters of the brain. Methods MR images of the employed digital phantom were realized with SimuBloch, a simulation package made for fast generation of image sequences based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 36 publications
3
82
0
Order By: Relevance
“…The impact of acquisition parameters on MRTA has been addressed in multiple studies. Ford et al, 69 using a digital 3D phantom, concluded that multiple texture features vary considerably between T1-weighted images (spin-echo, gradient echo, gradient recalled-echo, and inversion recovery) and T1 maps. They also noted that TR/TE variations on T1WI and T2WI affect texture features.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…The impact of acquisition parameters on MRTA has been addressed in multiple studies. Ford et al, 69 using a digital 3D phantom, concluded that multiple texture features vary considerably between T1-weighted images (spin-echo, gradient echo, gradient recalled-echo, and inversion recovery) and T1 maps. They also noted that TR/TE variations on T1WI and T2WI affect texture features.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Choline as a precursor of membrane metabolism is considered as a 1H MRS marker of membrane density, i.e., phospholipids synthesis and degradation [24]. Additionally, tCho is typically elevated during myelin sheet degradation [17,25] and an increase in tCho relative to tNAA and tCr was correlated with cerebral infarctions, ongoing gliosis, and ischemic and re/de-myelinization processes [19,25].…”
Section: Metabolic and Volumetric Changes In The Hippocampus After Mementioning
confidence: 99%
“…Additionally, tCho is typically elevated during myelin sheet degradation [17,25] and an increase in tCho relative to tNAA and tCr was correlated with cerebral infarctions, ongoing gliosis, and ischemic and re/de-myelinization processes [19,25]. It was recently shown that tCho was associated with membrane turnover that was directly related to Hcy removal [24], and a link was revealed between hHcy and ceramide metabolism in AD-type neurodegeneration [17,25,26]. In our experiments, we did not find significant changes in the levels of tCho and tCr in the hippocampus, but the rise in its ratio suggests for the proposed process of hippocampal re/de-remyelination, neuroglial dyshomeostasis, and cell membrane turnover in MDG conditions.…”
Section: Metabolic and Volumetric Changes In The Hippocampus After Mementioning
confidence: 99%
“…Pooling data from different centers is necessary, but it runs the risk of introducing bias to the values of texture features. Indeed, each step of the radiomics process can introduce variability independently from the intrinsic heterogeneity of the tumor; for instance: MRI field strength, manufacturers, coils, acquisition parameters, segmentation, voxel‐size resampling, normalization techniques, or gray‐level discretization . Previous studies have demonstrated that temporal parameters (ie, scan duration and temporal resolution) could significantly modify the ability to discriminate benign from malignant prostate or breast lesions, but they were based on average values of DCE‐MRI indices or morphology of the time–intensity curves.…”
mentioning
confidence: 99%
“…Indeed, each step of the radiomics process can introduce variability independently from the intrinsic heterogeneity of the tumor; for instance: MRI field strength, manufacturers, coils, acquisition parameters, segmentation, voxel-size resampling, normalization techniques, or gray-level discretization. [20][21][22][23] Previous studies have demonstrated that temporal parameters (ie, scan duration and temporal resolution) could significantly modify the ability to discriminate benign from malignant prostate or breast lesions, [24][25][26] but they were based on average values of DCE-MRI indices or morphology of the time-intensity curves. Only one study has focused on the stability of texture features extracted from computed tomography (CT) perfusion maps identifying an influence of temporal resolution.…”
mentioning
confidence: 99%